Pengaruh Green Accounting, Intellectual Capital dan Pengungkapan Lingkungan terhadap Nilai Perusahaan - Peachy Melvani, Gracia; Jansen Arsjah, Regina (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the effect of green accounting, intellectual capital, and environmental disclosure on firm value. This study uses a quantitative approach with secondary data obtained from annual report and sustainability report of energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sample of this research is companies in the energy sector listed on IDX with the observation year 2019-2023. Sampling was done by purposive sampling. The total sample examined consists of 109 data observations. This study uses descriptive statistical analysis, multiple data linear regression analysis, classical assumption test and hypothesis testingfor it analysis. The analytical tool to test the hypothesis uses the help of SPSS 29. The result of this study indicate that green accounting has no effect on firm value, intellectual capital has a positive effect on firm value, an environmrntal disclosure has no effect on firm value.